The association of inflammatory markers in early pregnancy with the development of gestational diabetes: Qazvin maternal and neonatal metabolic study (QMNS) - Sima Hashemipour; Seyedeh Sareh Kalantarian; Hamidreza Panahi; Sara Esmaeili Kelishomi; Amirabbas Ghasemi; Sarah Mirzaeei Chopani; Sepideh Kolaji; Milad Badri; Arefeh Ghobadi; Seyyed Mohammad Reza Hadizadeh Khairkhahan; Fatemeh Lalooha; Farideh Movahed; et al. (BMC Pregnancy and Childbirth)
Abstract Background This study investigates the association of blood cell components and blood cell-derived inflammatory indices in early pregnancy with the development of gestational diabetes mellitus (GDM). Methods This research is part of the Qazvin maternal and neonatal metabolic study (QMNMS) conducted in Iran from 2018 to 2021. Pregnant women with gestational age ≤ 14 weeks were enrolled in the study. The association of blood cells and inflammatory indices, including neutrophil-to-lymphocyte ratio (NLR), systemic inflammatory response index (SIRI), systemic immune inflammation index (SII), and aggregate systemic inflammatory response index (AISI), in early pregnancy with subsequent GDM development was examined using multivariate logistic regression. This analysis was adjusted for age, pre-pregnancy body mass index (BMI), weight gain, and GDM history in previous pregnancies (Model 1), as well as for these factors in addition to the homeostatic model assessment for insulin resistance (HOMA-IR) (Model 2). The correlation of blood cells and inflammatory indices with insulin resistance was assessed through Spearman partial correlation, adjusted for the same risk factors. Results The final analysis included 612 participants, among whom GDM developed in 96 participants (15.7%). Neutrophil, platelet, and lymphocyte counts showed significant correlations with HOMA-IR (r = 0.14, r = 0.22, and r = 0.17, respectively; P < 0.01 for all). In univariate analysis, the highest quartile of neutrophil count was associated with a 5.9 times higher risk of GDM development (95% CI 2.6–13.2, P < 0.001). In multivariate logistic regression, neutrophil count quartiles remained significant predictors of GDM development, with relative risks of 3.7, 4.4, and 8.2 for the 2nd, 3rd, and 4th neutrophil quartiles compared to the 1st quartile (P < 0.001). While platelet count was initially associated with GDM development (RR = 2.6, 95% CI 1.3–5.1, P = 0.028), this association was no longer significant after adjusting for HOMA-IR. Neither lymphocyte nor monocyte counts were linked to GDM development. Additionally, inflammatory indices, such as NLR, SIRI, SII, and AISI, did not provide additional predictive value for GDM development. Conclusion Neutrophil count is an independent predictor of GDM development, and its role in GDM development is not influenced by early pregnancy insulin resistance. Moreover, novel inflammatory indices offer no additional predictive benefit for GDM.